PEMBERSIHAN SAMPAH DI DASAR SUMUR MINYAK UNTUK MENINGKATKAN PRODUKSI - Agus Dwi Korawan; Drajat Indah Mawarni (SIMETRIS, 2018)
Oil wells in Ledok village, Blora regency are old wells from the Dutch era, the wells are managed by local community groups, Crude oil from the wells are taken by Pertamina, partners get rewarded according to the specified price. Partner in the Community Partnership Program (PKM) activities is L212 oil well, the chairman is Mr. Agus Purwanto. Based on the analysis of the situation, the problem in this well is that a lot of garbage at the bottom of the well, this garbage prevents the source of oil coming out, as a result the crude oil is produced a little. The purpose of the PKM program is to increase the ability of partners and increase crude oil production. The method used is discussion, training, and mentoring. The results obtained from the implementation of PKM are skills enhancement and increased production capacity